The Role of Colleges of Education at Yemeni Universities in Providing Student Teachers with the Twenty-First Century Skills - Al-Qawas, Mohammed Ahmed Morched; Al-Mansoori, Sinaa Kassem Ahmed (Journal of Educational and Psychological Sciences, 2020)
The study aims to identify the role of Colleges of Education at Yemeni universities in providing student teachers with twenty-first-century skills. The analytical descriptive approach was used. The two researchers designed a questionnaire that was distributed to a stratified random sample consisting of 169 male and female students from the student teachers at the fourth level of the two Colleges of Education at the Universities of Aden and Ibb. The results of the study showed that the degree of the acquisition of twenty-first-century skills among the student teachers in the Colleges of Education at the Universities of Aden and Ibb, at the level of the questionnaire, obtained an overall average (3.50 out of 5), which means a high degree. At the level of the areas, the communication skills area obtained the highest average (3.96), secondly, the area of life and job skills was with an average of (3.66), both of them had a (high) score; thirdly, thinking skills area was with an average of (3.37), and fourthly, professional skills area had an average of (3.27); finally, the area of the skills of using digital technology and computing culture obtained an average of (3.21), all of which had a (moderate) average. The results also revealed that there are no differences in the degree of student teachers’ acquisition of twenty-first-century skills, which are attributed to the variables of gender, specialization, and university. Based on the findings, the two researchers offered a number of recommendations. The most important of them are: It is necessary to develop the teacher preparation programs in the Colleges of Education at the Yemeni Universities in terms of curricula and teaching and evaluation strategies, and constantly reviewing to the extent to which such programs are consistent with the requirements and needs of the labor market and the sustainable development.